Changes in taxonomic and functional diversity of an urban stream fish assemblage: A 30-year perspective - Antoniazzi, Reuber; Montaña, Carmen G.; Peterson, David; Schalk, Christopher M. (Frontiers in Environmental Science, 2023)
Globally, freshwater fish diversity is rapidly changing in response to land use change, including urbanization. Time series of freshwater fish communities can help elucidate the underlying mechanisms of species loss and gains, as well as promote conservation strategies. Traditional approaches to understand the dynamics of fish assemblages is traditionally focused on taxonomic diversity, one aspect among many dimensions of biodiversity. Thus, using complementary analytical methods, such as functional diversity, can help researchers to develop a stronger predictive framework on the effects of the species loss or gains in response to urbanization. We assessed temporal changes of fish assemblages in an urban stream in East Texas between four seasonal surveys of 1989–1990 and 2018–2019. We explored the similarities and differences in species richness, composition, and functional diversity of fishes. Although the species richness and functional richness between the two time periods were similar, we observed changes in species composition. We also observed higher functional dispersion and evenness in the 2018–2019 assemblage compared to 1989–1990 assemblage. Some fish species were locally extirpated, while others colonized the system, increasing the functional diversity of the current assemblage. Urbanization has commonly been associated with declines in diversity and richness, however, our findings suggest that the addition of a few invasive generalist species (e.g., blue tilapia) and native tolerant (e.g., redbreast sunfish, blacktail shiner) in this stream system could be associated with increased human activities in this small, urbanized area in East Texas. Streams in East Texas support very diverse fish assemblages, with some sentinel species (e.g., imperiled shiners: Sabine shiner, a habitat-affinity, broadcast spawner) rapidly responding to stream alterations. Multiple stressors can underlie the dynamics and composition of fish assemblages; thus, it is essential for more comparative studies of current and historical data of fish assemblages. Likewise, studies targeting sentinel fish species may have more utility for the evaluation of freshwater ecosystems.